Serum levels of TNF-α, sIL-2R, IL-6, and IL-8 are increased and associated with elevated lipid peroxidation in patients with Behçet's disease - Cem Evereklioglu; Hamdi Er; Yusuf Türköz; Mustafa Çekmen (Mediators of Inflammation)
Aim: Behçet's disease (BD) is a systemic immuno-inflammatory disorder and the aetiopathogenesis is to be specified. Cytokines play a role in immune response and in many inflammatory diseases. The aim of this case-control study is to investigate serum pro-inflammatory cytokine tumour necrosis factor (TNF)-α, interleukin-1beta (IL-1β), soluble IL-2 receptor (sIL-2R), IL-6, and chemokine IL-8 levels in patients with BD. We also determined the end product of lipid peroxidation (malondialdehyde (MDA)) in BD patients as an index for oxidative stress.